Comb and Bottlebrush Polymers with Superior Rheological and Mechanical Properties - Abbasi, Mahdi (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 The Authors. Published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.